1980
DOI: 10.7601/mez.31.167
|View full text |Cite
|
Sign up to set email alerts
|

Description of a new species of Simulium (Simulium) Latreille and redescription of Simulium (Simulium) metallicum Bellardi from Guatemala : Diptera : Simuliidae

Abstract: The JapanSociety of Medical Entomology and Zoology (Jap. J. Sanit, Zool. Vol. 31 No. 3 p, 167-1791980] Description of a new species of Simulium (Simulium)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
Order By: Relevance
“…In Guatemala, Takaoka (1982) compared the larval distribution of S.metallicum s.s . with that of S.horacioi , a distinct member of the S.metallicum complex described from morphological criteria ( Okazawa & Onishi 1980). Grillet et al .…”
Section: Introductionmentioning
confidence: 99%
“…In Guatemala, Takaoka (1982) compared the larval distribution of S.metallicum s.s . with that of S.horacioi , a distinct member of the S.metallicum complex described from morphological criteria ( Okazawa & Onishi 1980). Grillet et al .…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising as these species are morphologically similar to S. metallicum, especially S. horacioi (see Shelley et al 2002: 175, Table 4). Simulium horacioi was described by Okazawa & Onishi (1980), although Takaoka (see Tada 1983) suggested that S. horacioi was a junior synonym of S. racenisi Ramírez Pérez. Later, Conn et al (1988Conn et al ( , 1989 described 11 sibling species within S. metallicum s.l.…”
Section: Resultsmentioning
confidence: 99%
“…Coscaron (1991) used head pattern as an important character for differentiating between some Neotropical species and variations in head pattern and body coloration of larvae have been used to distinguish both morphospecies, e.g. S. metallicum Bellardi from S. horacioi (=Okazawa & Onishi, 1980), and cytotypes of a species complex, e.g. S. metallicum (Conn et al, 1989;Millest, 1990).…”
Section: Introductionmentioning
confidence: 99%